Needle-knife papillotomy as a second step procedure - Celalettin ÇETİN and Sait BAĞCI and Ahmet UYGUN and Mustafa GÜLŞEN and Abdurrahman KADAYIFÇI and Necmettin KARAEREN and Kemal DAĞALP (Turkish Journal of Gastroenterology, 2019)
-